Syncope and presyncope in patients with COVID‐19. Issue 10 (12th September 2020) - Oates, Connor P.; Turagam, Mohit K.; Musikantow, Daniel; Chu, Edward; Shivamurthy, Poojita; Lampert, Joshua; Kawamura, Iwanari; Bokhari, Mahmoud; Whang, William; Miller, Marc A.; Choudry, Subbarao; Langan, Noelle; et al.
Abstract: Introduction: Recent studies have described several cardiovascular manifestations of COVID‐19 including myocardial ischemia, myocarditis, thromboembolism, and malignant arrhythmias. However, to our knowledge, syncope in COVID‐19 patients has not been systematically evaluated. We sought to characterize syncope and/or presyncope in COVID‐19. Methods: This is a retrospective analysis of consecutive patients hospitalized with laboratory‐confirmed COVID‐19 with either syncope or presyncope. This "study" group (n = 37) was compared with an age and gender‐matched cohort of patients without syncope ("control") (n = 40). Syncope was attributed to various categories. We compared telemetry data, treatments received, and clinical outcomes between the two groups. Results: Among 1000 COVID‐19 patients admitted to the Mount Sinai Hospital, the incidence of syncope/presyncope was 3.7%. The median age of the entire cohort was 69 years (range 26‐89+ years) and 55% were men. Major comorbidities included hypertension, diabetes, and coronary artery disease. Syncopal episodes were categorized as (a) unspecified in 59.4% patients, (b) neurocardiogenic in 15.6% patients, (c) hypotensive in 12.5% patients, and (d) cardiopulmonary in 3.1% patients with fall versus syncope and seizure versus syncope in 2 of 32 (6.3%) and 1 of 33 (3.1%) patients, respectively. Compared with the "control" group, there were no significant differences in both admission and peak blood levels of d‐dimer, troponin‐I, and CRP in the "study" group. Additionally, there were no differences in arrhythmias or death between both groups. Conclusions: Syncope/presyncope in patients hospitalized with COVID‐19 is uncommon and is infrequently associated with a cardiac etiology or associated with adverse outcomes compared to those who do not present with these symptoms.